Effect of Different Planting Systems on Dry Matter Production in Pearl millet + Legume Parallel Cropping Under Arid Rainfed Condition - Yadav, N D (Annals of Arid Zone, 2016)
The experiment conducted on a sandy loam soil during 1990 and 1992 revealed that parallel cropping of moth bean and cluster bean with pearl millet gave significantly higher total produce and total biological yield than their sole cropping during 1992. Among different planting systems parallel cropping of two rows of legumes with paired planted pearl millet (P + C 2:2) gave highest total biological yield than their sole cropping during both the years. Planting system, P + C (1:1) and P + C (2:2) gave highest total biological yield than their sole cropping during both the years. Planting system, P+ C (1:1) and P+C (2:2) gave an yield advantage of 137 and 126%, LER of 2.37 and 2.26 during 1990 and 1992, respectively.